Stochastic Maximum Principle for Optimal Control of Forward-Backward Stochastic Pantograph Systems with Regime Switching (Communications in Mathematical Research, 2021)
In this paper, we derive the stochastic maximum principle for optimalcontrol problems of the forward-backward Markovian regime-switching system. Thecontrol system is described by an anticipated forward-backward stochastic pantographequation and modulated by a continuous-time finite-state Markov chain. By virtueof classical variational approach, duality method, and convex analysis, we obtain astochastic maximum principle for the optimal control.